A Survey of Political Corruption in Mexico: Economic and Political Consequences - Carrillo Viramontes, José Antonio; Vazquez Guzman, David; Saldaña Hernández, Miriam; Ramos Soto, Ana Luz (Fondo Editorial de la Universidad Experimental Sur del Lago, Jesús María Semprum (UNE-SUR), Santa Bárbara del Zulia, Venezuela., 2024)
Using a systematic literature review approach, the aim of this chapter is to identify and describe the economic and political consequences of political corruption and accountability in Mexico in the last two decades. Though corruption is usually associated with underdeveloped countries in general, the Mexican case presents particular characteristics that are worth studying separately. Moreover, we identify in strict economic literature the determinants of the relationship between political systems and political corruption, and we describe the economic cost of political corruption. As the evidence suggests, the characteristics of the Mexican political system along with the hegemony, highly centralized public finances, and a lack of electoral punishment have increased Mexico’s political corruption, and, ultimately, reduced political accountability. Moreover, evidence suggest that Mexico is trapped in a corruption equilibrium that keeps self-reinforcing.